Diskursus Islam dan Hak Asasi Manusia (Kajian Universalitas dan Kasus Pelanggaran Hak Asasi Manusia) - Ahmad Muhtarom (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2017)
This paper explains the compatibility of islam and human rights as well as efforts to protect human rights ini Indonesia as a Muslim country. This paper thus rejects the opinion of a number of observers about the incompatibility or conflict between islam and human rights just because of the fact that the majority of muslim countries does not fully protect an enforce human rights. Since the beginning, islam has recognizied the protection of human rights, which were then formulated by the ulama with the concept of maqa>sid al-syari>’ah (objectives of shari’ah). As a muslim country, Indonesia in the reform era has committed to the protection and enforcement or human rights ini line with the impelementation of substantive democracy. Yet there remain a number of problems or obstacles in the protection of human rights caused by several factors, be they substantive, structural or cultural. The government, parliament as will as civil society an religious organizations have conducted efforts to solve the problem and obstacles.